Evaluation of Skills Assessment Processes in the Context of Small- and Medium-Sized Enterprises - Michaud, Guylaine; Savard, Reginald (Canadian Journal of Counselling and Psychotherapy, 2012)
This article presents the results of a study to evaluate the effects of 31 skills assessment processes (SA) based on the model developed by Michaud, Dionne, and Beaulieu (2007) and conducted among workers employed by 5 businesses in Quebec. The study used a mixed research method. Using a quasi-experimental approach, quantitative data were collected by way of questionnaires measuring self-efficacy, job retention, and self-esteem. The data were collected before the SA process, and again 2 weeks and 3, 6, and 12 months after the process. Qualitative data on the results of the process were collected at research interviews with participants and from process documents (portfolio, psychometric tests, interview summaries). Finally, triangulation of the results allowed the identification of effective interventions. The study’s evidence-based results validate the effectiveness of a skills assessment and development process in businesses. This type of process is useful to the employees, which suggests it may also benefit their employers, and offers a promising career development practice in line with lifelong learning.